Psychological rumination and recovery from work in intensive care professionals: associations with stress, burnout, depression and health. Issue 1 (December 2017) - Vandevala, Tushna; Pavey, Louisa; Chelidoni, Olga; Chang, Nai-Feng; Creagh-Brown, Ben; Cox, Anna
Abstract Background The work demands of critical care can be a major cause of stress in intensive care unit (ICU) professionals and lead to poor health outcomes. In the process of recovery from work, psychological rumination is considered to be an important mediating variable in the relationship between work demands and health outcomes. This study aimed to extend our knowledge of the process by which ICU stressors and differing rumination styles are associated with burnout, depression and risk of psychiatric morbidity among ICU professionals. Methods Ninety-six healthcare professionals (58 doctors and 38 nurses) who work in ICUs in the UK completed a questionnaire on ICU-related stressors, burnout, work-related rumination, depression and risk of psychiatric morbidity. Results Significant associations between ICU stressors, affective rumination, burnout, depression and risk of psychiatric morbidity were found. Longer working hours were also related to increased ICU stressors. Affective rumination (but not problem-solving pondering or distraction detachment) mediated the relationship between ICU stressors, burnout, depression and risk of psychiatric morbidity, such that increased ICU stressors, and greater affective rumination, were associated with greater burnout, depression and risk of psychiatric morbidity. No moderating effects were observed. Conclusions Longer working hours were associated with increased ICU stressors, and increased ICU stressors conferred greater burnout, depression and risk of psychiatric morbidity via increased affective rumination. The importance of screening healthcare practitioners within intensive care for depression, burnout and psychiatric morbidity has been highlighted. Future research should evaluate psychological interventions which target rumination style and could be made available to those at highest risk. The efficacy and cost effectiveness of delivering these interventions should also be considered.